2023
DOI: 10.1371/journal.pone.0293483
|View full text |Cite
|
Sign up to set email alerts
|

12-week concurrent brisk walking and Taijiquan (Tai Chi) improve balance, flexibility, and muscular strength of Chinese older women

Xiaorong Bai,
Wensheng Xiao,
Kim Geok Soh
et al.

Abstract: Healthy aging is a global goal to enhance the quality of life for older persons. This study evaluated the benefits of 12-week concurrent brisk walking and Taijiquan. Healthy Chinese women aged 60 years and above were enrolled to the control (n = 26) and intervention (n = 25) groups. Participants in the intervention group engaged in three exercise sessions per week for 12 weeks, whereas control group engaged in free-living activities. Each exercise session consisted of 20–45 minutes of walking and 20–45 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…As mentioned above, there are various culturally diverse exercises for developing balance control. Our recent randomized controlled experiment demonstrated that a multi-component exercise training program, comprising walking and Taijiquan, can enhance static balance, as well as improve flexibility, handgrip strength, and lower limb endurance in normotensive older persons ( 67 ). Hypertensive patients within the Chinese cultural radius thus can choose to practice a simplified form of Taijiquan, which typically lasts for approximately 15 min, to improve their balance control.…”
Section: Zero One Then All Thingsmentioning
confidence: 99%
“…As mentioned above, there are various culturally diverse exercises for developing balance control. Our recent randomized controlled experiment demonstrated that a multi-component exercise training program, comprising walking and Taijiquan, can enhance static balance, as well as improve flexibility, handgrip strength, and lower limb endurance in normotensive older persons ( 67 ). Hypertensive patients within the Chinese cultural radius thus can choose to practice a simplified form of Taijiquan, which typically lasts for approximately 15 min, to improve their balance control.…”
Section: Zero One Then All Thingsmentioning
confidence: 99%